Sustainability in the cruise industry: The case of listed companies - Mateus, Ana Lígia Vilela (2021)
The cruise industry, as any other hospitality and tourism market has been greatly affected by the COVID 19 pandemic, even so, and as we lean towards a ‘post pandemic’ scenario the 2030 Sustainability Objectives are still a priority. This study aims to understand the effects and the relationship that cruise companies adopting new environmentally friendly operations have on their financial net returns, and if this trend has been successfully adopted by listed cruise companies. Three different methodologies, will be implemented, using secondary data from the cruise companies Sustainability Reports, Annual Reports and Bloomberg platform. The Landrum’s five stages of Sustainability scale will be used, as well as an intensive report content analysis will be performed, and last descriptive analysis of values will be performed in order to provide a personalized view of each company ESG performance. GRI reporting companies publish less information on ESG values and activities. Bigger companies do publish more extensive information on CSR and ESG, rather than quality in content. ESG values are influenced by the company size, but company ROA or ROE showed no relationship with company ESG scores. The green tourism and ESG have been growing as important concepts in a tourist and traveller’s mind. Some studies have more recently started to investigate the steps companies are taking to follow the markets needs although a general conclusion has not been taken in the impact that ESG practices have on companies. With no other article or study found on the subject this study gives a tailored view on the subject as a pioneer investigation on the matter, using five important case studies on the industry.